Digital V-Card - The Future Security (International Journal of Innovative Research in Computer Science & Technology, 2020)
The paper focuses on designing and  developing a user interface to help out the community in  making a secure and also a better use of ATM cards using  virtual ATM card application. ATM cards are essential in  everyday life. Millions of ATM transactions take place in a  day. ATM cards are security less when it is lost or stolen. In  ATM cards, the PIN is essential and the user should  systematically change the PIN. The PIN should not be  shared with anyone. If a PIN is known to the hacker then it  very easy to use the ATM card. To resolve this the Virtual  ATM cards help more. The number of ATM card changes  after every transaction. This helps the user to keep the ATM  card number more securely for efficient cardless  transactions. The virtual ATM card project is implemented  using web technology and Android Studio software using  java language. Implementation can be done in 3 phases.  The first phase involving the design of the GUI for the  end-user to scan the QR image in the ATM, the second  phase deals with the implementation of a generation of  16-bit Random digit and third phase involves in connection  to the server by entering the pin, the bank server checks the  authentication and process the transaction. If the user using  the online payment for the transaction, then the user  requests the bank server for the ATM card number in the  Application. After the authentication, the bank server  provides the card number to the user. After the transaction,  the card number automatically will be destroyed and creates  a new card number for the user. The PIN can change, or it  can be auto-generated PIN by bank server so that the  security can be improved. Maintenance and further development of the application, as well as the feedback  provided by the end-users, are encouraged.
Keywords: Android App; Virtual ATM card; and QR code